Establishing a geochemical heterogeneity model for a contaminated vadose zone — Aquifer system - Murray, Christopher J.; Zachara, John M.; McKinley, James P.; Ward, Andy; Bott, Yi-Ju; Draper, Kate; Moore, Dean (Journal of contaminant hydrology, 2013)
A large set of sediment samples from a 1600m2 experimental plot within a 2.2km2 vadose zone and groundwater uranium (VI) plume was subject to physical, chemical, and mineralogic characterization. The plot is being used for field experimentation on U(VI) recharge and transport processes within a persistent groundwater plume that exists in the groundwater–river interaction zone of the Columbia River at the U.S. DOE Hanford site. The samples were obtained during the installation of 35 tightly spaced (10m separation) groundwater monitoring wells. The characterization measurements for each sample included total contaminant concentrations (U and Cu primarily), bicarbonate extractable U(VI), sequential 238U(VI) contaminant desorption Kd, 233U(VI) adsorption Kd, grain size distribution, surface area, extractable poorly crystalline Fe(III) oxides, and mineralogy. The characterization objective was to inform a conceptual model of coupled processes controlling the anomalous longevity of the plume, and to quantify the spatial heterogeneity of the contaminant inventory and the primary properties effecting reactive transport. Correlations were drawn between chemical, physical, and reaction properties, and Gaussian simulation was used to compute multiple 3-D realizations of extractable U(VI), the 233U(VI) adsorption Kd, and the distribution of the reactive <2mm fraction. Adsorbed contaminant U(VI) was highest in the vadose zone and the zone of seasonal water table fluctuation lying at its base. Adsorbed U(VI) was measureable, but low, in the groundwater plume region where very high hydraulic conductivities existed. The distribution of adsorbed U(VI) displayed no apparent correlation with sediment physical or chemical properties. Desorption [238U(IV)] and adsorption [233U(VI)] Kd values showed appreciable differences due to mass transfer controlled surface complexation and the effects of long subsurface residence times. The 233U(VI) adsorption Kd, a combined measure of surface complexation strength and site concentration, was relatively uniform throughout the domain, displaying correlation with fines distribution and surface area. The characterization results revealed U(VI) supplied to the groundwater plume through spatially heterogeneous recharge from residual contamination in the zone of seasonal water table fluctuation, and transport of U(VI) controlled by weak, kinetically-controlled surface complexation in the coarse-textured saturated zone. Geostatistical relationships for the adsorbed contaminant U distribution in the characterization domain allow an extrapolation to inventory at the plume scale, a critical unknown for remedial action. ► Conceptual model for distribution and behavior of uranium in persistent plume. ► Characterize coupled processes controlling the anomalous longevity of the plume. ► Complex environment linking vadose zone and fluctuating groundwater table. ► Geostatistical analysis of heterogeneity of uranium and reactive transport properties.